The impact of Remittances and Foreign Aid on Savings/Investment in Sub-Saharan Africa - (:unkn) unknown (My University, 2011)
Migrant remittances reached $21 billion in sub-Saharan Africa (SSA) in 2008 according to the World Bank estimates. Despite these important flows, few macroeconomic studies have been conducted on this topic in SSA compared to other developing regions. The existing studies on the impact of remittances in SSA have been mostly in the form of case studies at the microeconomic level or reports. The objective of this study is to fill in this gap by investigating the impact of remittances on savings and investment in respective samples of 37 and 34 SSA countries over the period 1980-2004. It also analyzes comparatively the effectiveness of remittances and foreign aid in promoting savings and investment. OLS and instrumental variables (2SLS) with country fixed-effects are used as estimations methods. We find that both remittances and foreign aid positively and significantly influence savings and investment in SSA, meaning that contrary to most conclusions found in the literature, migrant remittances in SSA are not only and entirely spent in basic consumption needs. We also find that, although the volume and share of remittances are lower than foreign aid, remittances have more positive impact on savings and investment. Remittances, by being directly received by people in need and not by governments as intermediaries, would serve more households' interests and be more effective in favouring economic development than foreign aid. However, when efficiently used in a good institutional, political and economic environment, foreign aid can act as a complement to remittances by allowing vulnerable households to have income above the threshold subsistence's level so they (or migrants) can use a larger share of remittances for savings and investment purposes. Our results also suggest that remittances may have indirect positive effects on growth in SSA through savings and investment.
Keywords: African Research